Cultivating Self-Directed Learning in Malaysian Higher Education: A Qualitative Inquiry - Ahmad Azmi Abdel Hamid Esmaeil; Peter Voo Su Kiong; Ismail Maakip; Balan Rathakrishnan; Murnizam Halik; Sanen Marshall; Dg Norizah Ag Kiflee @ Dzulkifli; Norzihan Ayub; Bavani Arumugam (Human Resource Management Academic Research Society, 2024)
Higher education institutions are increasingly moving away from traditional, lecture-centric teaching methods towards more student-driven approaches. This study delves into the promotion and application of self-directed learning in the Malaysian context. Through a qualitative research approach, we interviewed four lecturers and thirteen students from a specific Malaysian public university. The grounded theory was employed to analyze the data. Our findings indicate that fostering self-directed learning necessitates cultivating specific attitudes and behaviours in both students and the broader higher-education establishment. Students should be encouraged to find purpose in their lives, transition from a fear-based mindset to a critically assertive one, and embrace a sense of academic freedom. Conversely, lecturers need to refine their teaching methods by offering clearer explanations, adjusting their attitudes, and enhancing assessment techniques. Additionally, the system should grant lecturers greater flexibility in syllabus design and additional time for pedagogical development. A collaborative effort among lecturers, students, and policymakers is essential to embed self-directed learning in Malaysian universities